Judicial Law-Making in European Constitutional Courts - Florczak-Wątor, Monika (Comparative Constitutional Change, 2020)
This book analyses the speciﬁcity of the law-making activity of European constitutional courts. The main hypothesis is that currently constitutional courts are positive legislators whose position in the system of State organs needs to be redeﬁned. The book covers the analysis of the law-making activity of four constitutional courts in Western countries: Germany, Italy, Spain, and France; and six constitutional courts in Central–East European countries: Poland, Hungary, the Czech Republic, Slovak Republic, Latvia, and Bulgaria; as well as two international courts: the European Court of Human Rights (ECtHR) and the Court of Justice of the European Union (CJEU). The work thus identiﬁes the mutual interactions between national constitutional courts and international tribunals in terms of their law-making activity. The chosen countries include constitutional courts which have been recently captured by populist governments and subordinated to political powers. Therefore, one of the purposes of the book is to identify the change in the law-making activity of those courts and to compare it with the activity of constitutional courts from countries in which democracy is not viewed as being under threat. Written by national experts, each chapter addresses a series of set questions allowing accessible and meaningful comparison. The book will be a valuable resource for students, academics, and policy-makers working in the areas of constitutional law and politics.